Effectiveness of the stormwater quality devices to improve water quality at Putrajaya - Sidek L.M.; Basri H.; Noh M.N.M.; Ainan A.; Puad A.H.M. (Institute of Physics Publishing, 2023)
Development of Putrajaya has changed the character of the natural landform by covering the land with impervious surfaces. Houses, office buildings, commercial place and shopping centres have provided places to live and work. The route between buildings is facilitated and encouraged by a complex network of roads and car parks. However, this change from natural landforms and vegetative cover to impervious surfaces has major effect on stormwater which are water quality (non-point source pollution). This paper describes the effectiveness of the stormwater quality devices to improve water quality at selected Putrajaya for demonstration in order to evaluate low cost storm inlet type devices in the Putrajaya Catchment. Five stormwater quality devices were installed and monitored during the study. The devices include Ultra Drain Guard Recycle model, Ultra Curb Guard Plus, Ultra Grate Guard, Absorbent Tarp and Ultra Passive Skimmer. This paper will provide information on the benefits and costs of these devices, including operations and maintenance requirements. Applicability of these devices in gas stations, small convenience stores, residential and small parking lots in the catchment are possible due to their low cost. Published under licence by IOP Publishing Ltd.